2017
DOI: 10.15252/embj.201592481
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria control store‐operated Ca 2+ entry through Na + and redox signals

Abstract: Mitochondria exert important control over plasma membrane (PM) Orai1 channels mediating store-operated Ca 2+ entry (SOCE).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 82 publications
(155 reference statements)
9
83
2
Order By: Relevance
“…CRAC currents are mediated by the Orai protein family (ORAI1, 2 & 3), and their activation is regulated by STIM1 and STIM2 proteins, which are ER-localized Ca 2+ sensors [174-177]. In addition to the ER, mitochondria are involved in the regulation of SOCE, either due to their Ca 2+ buffering capability [178, 179] or through mitochondria-derived redox-signaling [180]. The plasma membrane, mitochondria and ER are associated with ROS production, and hence it is not surprising that redox regulation of ORAI channels and STIM proteins could be of importance in a variety of cell types.…”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
See 4 more Smart Citations
“…CRAC currents are mediated by the Orai protein family (ORAI1, 2 & 3), and their activation is regulated by STIM1 and STIM2 proteins, which are ER-localized Ca 2+ sensors [174-177]. In addition to the ER, mitochondria are involved in the regulation of SOCE, either due to their Ca 2+ buffering capability [178, 179] or through mitochondria-derived redox-signaling [180]. The plasma membrane, mitochondria and ER are associated with ROS production, and hence it is not surprising that redox regulation of ORAI channels and STIM proteins could be of importance in a variety of cell types.…”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
“…Indeed, it was demonstrated that forced expression of NCLX could increase mitochondrial oxidation of the redox sensitive RoGFP probe and abrogate histamine-induced increases in mitochondrial Ca 2+ and NAD(P)H, presumably through its role in decreasing mitochondrial Ca 2+ levels and hence inhibiting matrix dehydrogenase activity [263]. Recently, the consequences of this mitochondrial ROS-NCLX interplay were further explored using a model of NCLX knock-down [180]. In this study, it was demonstrated that knockdown of NCLX increases mitochondrial ROS production by enhancing mitochondrial Ca 2+ levels and that this mediates inhibition of the CRAC channel ORAI1.…”
Section: Redox Regulation Of Er and Mitochondrial Ca2+ Modulatorsmentioning
confidence: 99%
See 3 more Smart Citations